Some Remarks regarding the Criminalization and the Forensic Investigation of the Crime of Computer Forgery in the Romanian Legislation - Adrian Cristian Moise (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
The article presents and analyzes issues related to the criminalization of the offence of computer forgery, provided by the Article 325 of the Romanian Criminal Code, as well as issues related to the criminalization of the offence of computer forgery in the main legal instrument in the field of combating cybercrime at the European level: the Council of Europe Convention on Cybercrime.Moreover, the article also mentions some aspects related to the criminalization of the crime of computer forgery in some countries of the European Union. Finally, this study also presents the main issues to be clarified in the forensic investigation process of the crime of computer forgery.